2009
DOI: 10.1021/bi900122r
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosyl Hydride (HNO) as an O2 Analogue: Long-Lived HNO Adducts of Ferrous Globins

Abstract: Nitrosyl hydride, HNO or nitroxyl, is the one-electron reduced and protonated form of nitric oxide. HNO is isoelectronic to singlet O 2 , and we have previously reported that deoxy myoglobin traps free HNO to form a stable adduct. In this report, we demonstrate that oxygen-binding hemoglobins from human, soy and clam also trap HNO to form adducts which are stable over a period of weeks. The same species can be formed in higher yield by careful reduction of the ferrous nitrosyl adducts of the proteins. Like the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
99
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(112 citation statements)
references
References 40 publications
(83 reference statements)
13
99
0
Order By: Relevance
“…Probably the most distinguishing and diagnostic characteristic of the ferrous myoglobin HNO complexes is the 1 H NMR resonance for the bound HNO at about 15 ppm. The HNO adducts with ferrous myoglobin are inherently stable under strict anaerobic conditions and can be stored for extended periods of time without degradation [29]. However, exposure of the ferrous HNO myoglobin complex to O 2 results in rapid ferric myoglobin formation and exposure to NO or NO 2 − gives a ferrous-NO complex [28].…”
Section: Reactions Of Hno With Iron Heme Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably the most distinguishing and diagnostic characteristic of the ferrous myoglobin HNO complexes is the 1 H NMR resonance for the bound HNO at about 15 ppm. The HNO adducts with ferrous myoglobin are inherently stable under strict anaerobic conditions and can be stored for extended periods of time without degradation [29]. However, exposure of the ferrous HNO myoglobin complex to O 2 results in rapid ferric myoglobin formation and exposure to NO or NO 2 − gives a ferrous-NO complex [28].…”
Section: Reactions Of Hno With Iron Heme Proteinsmentioning
confidence: 99%
“…However, exposure of the ferrous HNO myoglobin complex to O 2 results in rapid ferric myoglobin formation and exposure to NO or NO 2 − gives a ferrous-NO complex [28]. Interestingly, it appears that the ferrous HNO myoglobin adduct can react with excess HNO to also give the NO adduct (Reaction 8) [29]. Of particular note is the possibility that a ferrous-HNO complex in sGC could be converted to the ferrous-NO complex by a variety of species (i.e.…”
Section: Reactions Of Hno With Iron Heme Proteinsmentioning
confidence: 99%
“…Free HNO is quite reactive and short-lived in aqueous solution [12], but we have shown that an HNO adduct of ferrous myoglobin, HNO-Mb can be formed by reduction of NO-Mb [13,14], by trapping of free HNO by deoxymyoglobin (deoxyMb or Mb-Fe II ) [15], or by treatment of metmyoglobin (metMb or Mb-Fe III ) with salts of nitrite and borohydride [16]. This stable ferrous heme adduct has been characterized by 1 H NMR [17], 1 H-15 N heteronuclear single quantum coherence (HSQC) [18], as well as resonance Raman and X-ray absorption spectroscopies [19]. As HNO is isoelectronic with O 2 and forms stable diamagnetic adducts with ferrous hemoglobins from various species, we have suggested its use as an O 2 analog [18].…”
Section: Introductionmentioning
confidence: 99%
“…This stable ferrous heme adduct has been characterized by 1 H NMR [17], 1 H-15 N heteronuclear single quantum coherence (HSQC) [18], as well as resonance Raman and X-ray absorption spectroscopies [19]. As HNO is isoelectronic with O 2 and forms stable diamagnetic adducts with ferrous hemoglobins from various species, we have suggested its use as an O 2 analog [18]. Most recently, we have shown that HNO may replace O 2 during turnover of a non-heme Mn dioxygenase enzyme, quercetin dioxygenase; this nitroxygenase activity results in the regioselective incorporation of the N atom derived from HNO within the enzymatic product [20].…”
Section: Introductionmentioning
confidence: 99%
“…15 ppm, well away from other protein resonances, which allowed structural characterization of the heme pocket by 2D NOE and COSY experiments (10). Other ferrous globins also rapidly trap free HNO to directly yield stable HNO adducts, identifiable by changes in electronic absorbances as well as unique 1 H and 15 N NMR resonances due to the nitrosyl hydride (11).…”
mentioning
confidence: 99%